2018
DOI: 10.1007/s11940-018-0510-9
|View full text |Cite
|
Sign up to set email alerts
|

Current Treatment Options for Peripheral Nerve Hyperexcitability Syndromes

Abstract: Current therapy options are based on symptomatic management as well as focusing the underlying immune/genetic/paraneoplastic pathology by immunosuppressants, chemotherapy, and surgery. Further research is desired to provide treatment options geared specifically towards addressing PNH. Supportive care can also be an area for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…8 Its persistence in sleep and normal electroencephalogram pegs the location of the pathology in the terminal axonal branches, hence central causes such as stiff person syndrome, seizures, or cerebellar lesions may be unlikely. 2,8 The unremarkable neoplastic workup, in addition to the absence of other autoimmune disorder signs and symptoms, render our patient to have a primary Isaac syndrome. This may also explain the negative anti-VGKC complex antibodies in our case because these are usually associated with small-cell lung cancer, thymoma, and autoimmune diseases.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…8 Its persistence in sleep and normal electroencephalogram pegs the location of the pathology in the terminal axonal branches, hence central causes such as stiff person syndrome, seizures, or cerebellar lesions may be unlikely. 2,8 The unremarkable neoplastic workup, in addition to the absence of other autoimmune disorder signs and symptoms, render our patient to have a primary Isaac syndrome. This may also explain the negative anti-VGKC complex antibodies in our case because these are usually associated with small-cell lung cancer, thymoma, and autoimmune diseases.…”
Section: Discussionmentioning
confidence: 81%
“…1 Although this syndrome has been associated with anti-Voltage Gated K-Channels antibodies [antileucine-rich glial inactivated 1 (LGI-1) and anti-contactin-associated protein 2 (Caspr2) antibodies], the sensitivity of detecting this antibody is only 35%, and further confirmation is still guided by detection of spontaneous discharges such as fasciculations, myokymia, or neuromyotonia in electromyogram (EMG). 1,2 However, EMG is limited by its invasiveness and machine and specialist availability, especially in low-to-middleincome countries (LMIC). Thus, a new alternative diagnostic tool may be needed.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it could be the case that a denervation hypersensitivity following lasting intake of mexiletine triggered the symptoms occurring after the discontinuation of the drug, rather than inducing an autoimmune reactivation. [ 47 50 ] About that, experimental studies have shown that Na v are over-expressed beyond the nodal-paranodal sites in the growing and sprouting axons, as well as following functional denervation. Such a remodeling of Na v largely results in altered axonal and, consequently, muscle excitability.…”
Section: Discussionmentioning
confidence: 99%
“…There were reports of good efficacy of sodium channel blockers such as carbamazepine and phenytoin in reducing muscle stiffness, twitching, and cramps [32]. Carbamazepine is usually preferred because it is easier to use and can be administered at increasing dosage until the resolution of symptoms, up to 1600 mg/ day [67]. Gabapentin and acetazolamide were also reported effective in case reports [68][69][70].…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%